The Impact of Marketing Mix Factors on Thai Foods’ Buying Behavior of Chinese Tourists - Lyu, Bing; Vanichkul, ฺNatanuj (Al-HIKMAH Journal, 2021)
The objective of this research is to study marketing mix factors affecting Thai foods’ buying behavior of Chinese tourists. This study used a quantitative research approach using online questionnaires to collect data from 400 samples of Chinese tourists, who travelled to Thailand in 2019, by convenience sampling methods. Descriptive statistics: frequency and percentage were used to analyze the demographic characteristics of respondents. Mean and standard deviations were used to analyze opinions of Chinese tourists on marketing mix factors affecting Thai foods’ buying behavior. Inferential statistics using multiple regression was used to test the hypotheses of marketing mix factors affecting Thai foods’ buying behavior of Chinese tourists. This study revealed that price, place, and promotion factors had an impact on the average spending of Chinese tourists on Thai foods at a statistical significance level of 0.05. Price factor affected the proportion of spending by Chinese tourists on Thai foods at a statistical significance level of 0.05. Product factor also affected the proportion of Thai food meals purchased by Chinese tourists at a statistical significance level of 0.05.